Cooperation of N- and C-terminal substrate transmembrane domain segments in intramembrane proteolysis by γ-secretase - Nadine T. Werner; Philipp Högel; Gökhan Güner; Walter Stelzer; Manfred Wozny; Marlene Aßfalg; Stefan F. Lichtenthaler; Harald Steiner; Dieter Langosch (Communications Biology, 2023)
Deuterium/hydrogen exchange shows that conformational flexibility of the hybrid transmembrane domains (TMD) of amyloid precursor proteins plays a role in TMD cleavability by γ-secretase in vitro and in cellulo.